Chaplains of the king in the colonial Philippines: archbishoprics and unstable authority, 1595-1653 - Coello de la Rosa, Alexandre (Palgrave Macmillan, 2025)
"The first of two volumes on the archbishops and cathedral chapters of seventeenth-century Manila, this book fills a historiographical gap by examining the diocesan clergy of the Philippines' political maneuverings. In particular, this volume studies the archbishops' unstable authority and ecclesiastical chapters' preeminence at this time. First, it emphasizes the need for a new paradigm of conflict-ridden Catholic evangelization--ius predicandi--that explores the interactions and engagements of the Church's legal agents, mainly priests, canons, and bishops, and brings their rivalries to the fore. Second, it draws attention to one of the most neglected topics in Philippine ecclesiastical history, namely the metropolitan cathedral chapters, which, far from being monolithic units at the service of their archbishops, were too highly fragmented to constitute a single power holder. This volume's examination of these power dynamics makes it clear that history of the colonial Catholic Church cannot be separated from political history of the Philippines." --